(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Water is essential to all living creatures, especially to humans. Due to its importance, the need for clean and safe water increases day by day. However, the world, particularly the Philippines, faces major problems regarding water contamination and water consumption. Many Filipinos have been diagnosed with diseases caused by water contamination. A published study also stated that in the future, the Philippines would suffer water shortage. The researchers became determined to solve these problems by providing machinery and equipment designed for water filtration. The business also promotes the idea of utilizing rainwater as a water supply. Water Master Philippines aims to provide aid to eradicate the situation regarding water contamination and helps to remedy the future problem of water shortage. The method used for this study was qualitative analysis. The researchers surveyed 30 respondents, composed by the representative of family (18), school (7), and food industry (5) around Medium Rise Building Compound, Pilot Drive, Brgy. Commonwealth, Quezon City. The researchers used 4Ps as the basis for this survey. The purpose of this survey was to identify if the target market will patronize the products and services and serve as a guide on what would be the best action researchers should take to meet and exceed customer satisfaction. This study also used the financial statement to determine the business’s capability in terms of earning and meeting its obligations. The results of this study showed business effectiveness to its respected target market, thereby indicating that the business product and services offering was significant to the problems stated. In terms of the financial aspect, Water Master Philippines is truly profitable, although the product and services are somehow technical. The business earning was enough to fulfill its obligations and had a stout return on investment. The results also indicated that the business has well-organized management and can survive intense competition. The researchers found out that the business has a strong impact on its target market and gaining higher sales from tangible products. Therefore, the researchers recommend investing more capital for tangible products such as filters, carbon blocks, elements, and machines. The owner should also engage in different expos that would showcase the importance of business offerings and create more promotional activities to build strong branding and earn higher profit for future expansion.